FATIGUE LIFE AND RELIABILITY ANALYSIS OF CYCLOIDAL GEARS BASED ON WorkBench AND nCode (Jixie qiangdu)
As one of the core parts of RV reducer,the fatigue life of cycloidal gears has an important impact on the life of the whole reducer.WorkBench finite element analysis was used to determine the contact stress state and structural weak points of the cycloid gear.On this basis,the mathematical model of contact fatigue life of cycloidal gears was established by Miner linear damage accumulation theory and S-N curve correction theory,and then nCode Designlife,a fatigue life analysis software,was used to analyze the contact fatigue life of cycloidal gears with the maximum contact stress,and the result was 7.6%different from the design life of cycloidal gears under the same load condition.The maximum point of contact fatigue damage of the cycloidal gear was determined.Finally,the reliability of the cycloidal gear was determined based on the contact fatigue life analysis data,which provides a reference for the structural optimization design and reliability analysis of the cycloidal gear.